2022
DOI: 10.1111/jsr.13569
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risk of COVID‐19 exposure and poor COVID‐19 prognosis impair sleep: The mediating and moderating roles of COVID‐19‐related anxiety and knowledge

Abstract: The ongoing COVID‐19 pandemic has been linked to increased levels of stress, depression, and anxiety in many people around the world. Therefore, identifying individuals at risk of psychosocial burden during this unprecedented crisis is essential for developing prevention measures and treatment options for mental health issues. To this aim, we investigated two risk groups: individuals at higher risk of exposure to the virus and individuals at higher risk of poor prognosis if they contract the virus. We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
(56 reference statements)
0
6
0
4
Order By: Relevance
“…Several possible causes for disturbed sleep in post‐COVID syndrome have been discussed. These include stress and anxiety caused by the social consequences of the pandemic [15]. Fernández‐de‐las‐Peñas et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several possible causes for disturbed sleep in post‐COVID syndrome have been discussed. These include stress and anxiety caused by the social consequences of the pandemic [15]. Fernández‐de‐las‐Peñas et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several possible causes for disturbed sleep in post-COVID syndrome have been discussed. These include stress and anxiety caused by the social consequences of the pandemic [15]. Fernández-de-las-Peñas et al [7] showed an association between anxiety and depression scores and sleep quality measured by the PSQI in patients with post-COVID syndrome.…”
Section: Sleep and Covid-19mentioning
confidence: 99%
“…65 With the impact of the COVID-19 pandemic on negative affect and bedtime procrastination of Chinese college students, the present findings supported these suggestions from the literature and highlight that the COVID-19 outbreak is a common risk factor for mental health and sleep problems across different populations and contexts. 14,[66][67][68][69] The Relationship Between COVID-19 Related Emotional Stress and Bedtime Procrastination First, the study found that COVID-19 related emotional stress was related to bedtime procrastination. It was consistent with existing research, indicating that lockdown was associated with later bedtime across different continents.…”
Section: Discussionmentioning
confidence: 99%
“…All items are divided into two dimensions, sleep problems, and daytime functioning, and can be calculated for both subscales and the total scale score, with higher scores indicating more severe sleep quality problems ( Sattler, Seddig & Zerbini, 2021 ). The scale has been used in studies of sleep related to COVID-19 and has demonstrated good utilization ( Zerbini et al, 2022 ). The Chinese version of the questionnaire used by the participants consists of six items, constituting the two dimensions.…”
Section: Methodsmentioning
confidence: 99%